Self to self, self to others: a cognitive bridge between mirror self-recognition and empathy in non-human animals - Swygert, Paige, author; Dewey, Tanya, advisor; Willis, Jennie, committee member (Colorado State University. Libraries, 2025)
Understanding animal consciousness remains one of the most compelling and controversial challenges in behavioral science. This thesis explores the intersection of self-recognition and empathy in non-human animals, focusing on the cognitive and emotional capacities that underpin these traits. Although research in animal behavior has advanced considerably, there remains a reluctance to attribute consciousness to animals due to methodological limitations and philosophical hesitations. By examining the development and application of the mirror self-recognition (MSR) test—from its origin in great apes to its use in dolphins, birds, ants, and beyond—this study investigates the nuances of what it means for an animal to recognize itself and whether that recognition indicates broader self-awareness. A central theme is the distinction between self-recognition (an understanding of the physical self) and self-awareness (an understanding of the self in relation to others), a distinction crucial in evaluating empathy. Drawing on theories such as Frans de Waal's "Russian-doll model," the thesis explores the evolutionary significance of empathy, its relationship to cognitive complexity and encephalization, and its manifestation through behaviors like contagious yawning, consolation, and targeted helping. Notably, many animals that pass the MSR test also exhibit empathetic behaviors, suggesting a potential cognitive link between recognizing the self and relating to the emotional states of others. This thesis argues that self-awareness may be a prerequisite for higher forms of empathy, though the presence of prosocial behavior without confirmed self-recognition complicates this relationship. The implications of these findings are far-reaching, impacting fields from animal welfare and conservation to ethics in agriculture and biomedical research, and ultimately challenge long-held assumptions, calling for a reevaluation of how humans treat and value non-human lives.
Biology department
Advisor: Dr. Tanya Dewey
Committee: Dr. Jennie Willis
Keywords: mirror self-recognition; self-awareness; empathy; animal behavior; theory of mind